Preparation and Characterization of Carbon Paste Electrode Bulk-Modified with Multiwalled Carbon Nanotubes and Its Application in a Sensitive Assay of Antihyperlipidemic Simvastatin in Biological Samples - Ashrafi, Amir M; Richtera, Lukáš (Molecules (Basel, Switzerland), 2019)
Determination of an antihyperlipidemic drug simvastatin (SIM) was carried out using a carbon paste electrode bulk-modified with multiwalled carbon nanotubes (MWCNT-CPE). Scanning electrochemical microscopy (SECM), scanning electron microscopy (SEM), and atomic force microscopy (AFM) were used for the characterization of the prepared electrodes. Different electrodes were prepared varying in mass percentage of MWCNTs to find out the optimum amount of MWCNTs in the paste. The MWCNT-CPE in which the mass percentage of MWCNTs was 25% (w/w) was found as the optimum. Then, the prepared electrode was used in a mechanistic study and sensitive assay of SIM in pharmaceutical dosage form and a spiked human plasma sample using differential pulse voltammetry (DPV). The prepared electrode shows better sensitivity compared to the bare carbon paste and glassy carbon electrode (GCE). The detection limit and the limit of quantification were calculated to be 2.4 × 10-7 and 8 × 10-7, respectively. The reproducibility of the electrode was confirmed by the low value of the relative standard deviation (RSD% = 4.8%) when eight measurements of the same sample were carried out. Determination of SIM in pharmaceutical dosage form was successfully performed with a bias of 0.3% and relative recovery rate of 99.7%. Furthermore, the human plasma as a more complicated matrix was spiked with a known concentration of SIM and the spiking recovery rate was determined with the developed method to be 99.5%.
Keywords: multiwalled carbon nanotube; scanning electrochemical microscopy; carbon paste electrode; biological sample; mechanism study; elektrody; lidé; mikroskopie elektronová rastrovací; Electrodes; Carbon; uhlík; simvastatin; Nanotubes, Carbon; simvastatin determination; Simvastatin; Microscopy, Electron, Scanning; nanotrubičky uhlíkové; Humans